2017
DOI: 10.1016/j.jvs.2017.03.439
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative delirium in patients undergoing vascular surgery

Abstract: This study has confirmed that PODE after vascular surgery procedures is a multifactorial disease, and several independent risk factors have been identified. However, pooled data regarding the effect of PODE on primary outcomes after vascular surgery procedures are still lacking. The results of this review could contribute to the designation of future prediction models and improve prevention of PODE in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 41 publications
4
41
2
1
Order By: Relevance
“…Moreover, in our population male sex was associated with delirium. Contrasting results are reported in literature, concerning gender as a risk factor for delirium, but evidence referring to different clinical settings suggests that men have a significantly higher chance of developing delirium [41][42][43]. Referring to fracture patients, greater levels of cognitive impairment within the first days of hip fracture have been reported in male patients [44].…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, in our population male sex was associated with delirium. Contrasting results are reported in literature, concerning gender as a risk factor for delirium, but evidence referring to different clinical settings suggests that men have a significantly higher chance of developing delirium [41][42][43]. Referring to fracture patients, greater levels of cognitive impairment within the first days of hip fracture have been reported in male patients [44].…”
Section: Discussionmentioning
confidence: 61%
“…13,18 A recent systematic review of patients undergoing vascular surgery also showed that ICU admission was a strong independent risk factor for postoperative delirium. 34 There is limited literature assessing the ability of the Clinical Frailty Scale to predict specific clinical outcomes such as delirium. 35 However, the scale does take into consideration, both directly and indirectly, components that have been established as independent risk factors for delirium, including functional status, comorbid disease burden and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…28 Galyfos et al showed that preoperative neurological disease was an independent risk factor for postoperative delirium. 29 The reasons why mental illness has an adverse effect after cardiac surgery are thought to be as follows. These patients are considered to have a worse baseline risk factor compared with those without mental illness.…”
Section: Discussionmentioning
confidence: 99%